2004
DOI: 10.2527/2004.82123415x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci analysis for growth and carcass traits in a half-sib family of purebred Japanese Black (Wagyu) cattle1

Abstract: We used a half-sib family of purebred Japanese Black (Wagyu) cattle to locate economically important quantitative trait loci. The family was composed of 348 fattened steers, 236 of which were genotyped for 342 microsatellite markers spanning 2,664 cM of 29 bovine autosomes. The genome scan revealed evidence of 15 significant QTL (<5% chromosome-wise level) affecting growth and carcass traits. Of the 15 QTL, six QTL were significant at the 5% experiment-wise level and were located in bovine chromosomes (BTA) 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 20 publications
6
61
3
Order By: Relevance
“…Maltecca et al (2009) recently identified a birth weight QTL at 19 cM on chromosome 14 in a Jersey-Holstein cross. There are also reports on QTL for postnatally measured growth traits in Wagyu (Mizoshita et al 2004, Takasuga et al 2007) and a Jersey-Limousin cross (Morris et al 2002), indirectly supporting our suggestive evidence for a secondary pCE QTL on chromosome 14. Casas et al (2003) and Davis et al (1998) identified a QTL for birth weight in the very proximal region of chromosome 21 in crosses of Brahman with Hereford and Charolais, respectively, providing supportive evidence for the pCE QTL identified in this study.…”
Section: à036supporting
confidence: 87%
“…Maltecca et al (2009) recently identified a birth weight QTL at 19 cM on chromosome 14 in a Jersey-Holstein cross. There are also reports on QTL for postnatally measured growth traits in Wagyu (Mizoshita et al 2004, Takasuga et al 2007) and a Jersey-Limousin cross (Morris et al 2002), indirectly supporting our suggestive evidence for a secondary pCE QTL on chromosome 14. Casas et al (2003) and Davis et al (1998) identified a QTL for birth weight in the very proximal region of chromosome 21 in crosses of Brahman with Hereford and Charolais, respectively, providing supportive evidence for the pCE QTL identified in this study.…”
Section: à036supporting
confidence: 87%
“…The interval flanked by markers DIK4782 and IGF-1 harbors QTL reported for carcass yield (Mizoshita et al, 2004), fat depth and retail product yield (Casas et al, 2000), dressing percentage (Stone et al, 1999;MacNeil and Grosz, 2002), and rib bone and fat (Stone et al, 1999). Quantitative trait loci for growthrelated traits have also been identified in this chromosomal region (Davis et al, 1998;Stone et al, 1999;Kim et al, 2003;Machado et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The search for QTL affecting carcass yield and carcass composition in cattle has been mainly conducted by studying commercial half-sib families (Mizoshita et al, 2004;Mizoguchi et al, 2005) or experimental crosses [e.g., Bos indicus × Bos taurus (Stone et al, 1999;Casas et al, 2003) and Limousin × Wagyu cattle (Alexander et al, 2007)]. In the case of experimental cross populations, the QTL model used is based on the assumption that the founder lines are fixed for alternative alleles at the QTL (Haley et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…These finding demonstrate that NPY gene is an excellent biological candidate gene for body weight, carcass traits or growth-related traits in livestock. Mizoshita et al (2004) also reported QTL identified on BTA4 in the region of bovine NPY for marbling and lean meat area. Therefore, it is possible that these NPY SNPs are linked to these QTL (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%